2019
DOI: 10.21203/rs.2.18446/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and outcomes of a comprehensive multidisciplinary incidental lung nodule and lung cancer screening program

Abstract: BackgroundAppropriate management of lung nodules detected incidentally or through lung cancer screening can increase the rate of early-stage diagnoses and potentially improve treatment outcomes. However, the implementation and management of comprehensive lung nodule programs is challenging. MethodsA single-center, retrospective study was conducted to describe the development and outcomes of a lung nodule program at a community practice in Tennessee.ResultsThe number of patients with lung nodules referred to th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Consequently, this screening method has been accepted by the academic community and included in clinical guidelines. With large-scale CT screening, an increasing number of unidentified lung lesions appears to be occurring (4,5). Therefore, the optimal diagnostic approach for patients with suspicious nodules urgently needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this screening method has been accepted by the academic community and included in clinical guidelines. With large-scale CT screening, an increasing number of unidentified lung lesions appears to be occurring (4,5). Therefore, the optimal diagnostic approach for patients with suspicious nodules urgently needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The studies rated with the highest quality and strength supported that smoking history was associated with an increased risk of lung cancer. The literature review confirmed the decision to adopt the 2013 USPSTF recommendations 20–25…”
Section: Methodsmentioning
confidence: 74%
“…In most cases, no growth is observed after one or two additional scans and malignancy can be ruled out. Only in about 2% of patients an invasive diagnostic test becomes necessary during follow-up, leading to the diagnosis of a lung cancer in approximately half of them [16]. The burden of additional tests with routine preoperative CT thus consists mainly of additional non-invasive follow-up.…”
Section: Discussionmentioning
confidence: 99%